The Effects of Age-of-Acquisition on Ambiguity Resolution: Evidence from Eye Movements - Barbara J. Juhasz; Margaret M. Gullick; Leah W. Shesler (Bern Open Publishing, 2011)
Words that are rated as acquired earlier in life receive shorter fixation durations than later acquired words, even when word frequency is adequately controlled (Juhasz & Rayner, 2003; 2006). Some theories posit that age-of-acquisition (AoA) affects the semantic representation of words (e.g., Steyvers & Tenenbaum, 2005), while others suggest that AoA should have an influence at multiple levels in the mental lexicon (e.g. Ellis & Lambon Ralph, 2000). In past studies, early and late AoA words have differed from each other in orthography, phonology, and meaning, making it difficult to localize the influence of AoA. Two experiments are reported which examined the locus of AoA effects in reading. Both experiments used balanced ambiguous words which have two equally-frequent meanings acquired at different times (e.g. pot, tick). In Experiment 1, sentence context supporting either the early- or late-acquired meaning was presented prior to the ambiguous word; in Experiment 2, disambiguating context was presented after the ambiguous word. When prior context disambiguated the ambiguous word, meaning AoA influenced the processing of the target word. However, when disambiguating sentence context followed the ambiguous word, meaning frequency was the more important variable and no effect of meaning AoA was observed. These results, when combined with the past results of Juhasz and Rayner (2003; 2006) suggest that AoA influences access to multiple levels of representation in the mental lexicon. The results also have implications for theories of lexical ambiguity resolution, as they suggest that variables other than meaning frequency and context can influence resolution of noun-noun ambiguities.